Effect of Chain‐End Chemistries on the Efficiency of Coupling Antibodies to Polymers Using Unnatural Amino Acids. Issue 21 (16th September 2020) - Sivaram, Amal J.; Wardiana, Andri; Preethi, S. S. Hema; Fuchs, Adrian V.; Howard, Christopher B.; Fletcher, Nicholas L.; Bell, Craig A.; Thurecht, Kristofer J.
Abstract: Novel conjugates that incorporate strategies for increasing the therapeutic payload, such as targeted polymeric delivery vehicles, have great potential in overcoming limitations of conventional antibody therapies that often exhibit immunogenicity and limited drug loading. Click chemistry has significantly expanded the toolbox of effective strategies for developing hybrid polymer‐biomolecule conjugates, however, effective systems require orthogonality between the polymer and biomolecule chemistries to achieve efficient coupling. Here, three cycloaddition‐based strategies for antibody conjugation to polymeric carriers are explored and show that a purely radical‐based method for polymer synthesis and subsequent biomolecule attachment has a trade‐off between coupling efficiency of the antibody and the ability to synthesize polymers with controlled chemical properties. It is shown that careful consideration of both coupling chemistries as well as the potential effect of how this modulates the chemical properties of the polymer nanocarrier should be considered during the development of such systems. The strategies described offer insight into improving conjugate development for therapeutic and theranostic applications. In this system, polymerization using conventional and established reversible addition fragmentation chain transfer (RAFT) agents, followed by multiple post‐modification steps, always leads to systems with more defined chemical architectures compared to strategies that utilize alkyne‐functional RAFT agents. Abstract : Three cycloaddition strategies for antibody conjugation to polymeric carriers are explored, showing there is a trade‐off between coupling efficiency of the antibody and the ability to synthesize polymers with controlled chemical properties. Ultimately, radical‐based polymerization and strained alkyne functionality need to be segregated from one another in order to achieve high functional alkyne content.